1999
DOI: 10.1111/j.1348-0421.1999.tb02446.x
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Lymphocytes in the Bone Marrow, Thymus and Extrathymic T Cells in the Liver Are Generated In Situ from Their Own Preexisting Precursors

Abstract: Parabiotic pairs of B6.Ly5.1 and B6.Ly5.2 mice were used to investigate how lymphocytes in various organs and various lymphocyte subsets mixed with partner cells. The origin of partner cells was determined by using anti-Ly5.1 mAb in conjunction with immunofluorescence tests. Parabiosis was also produced after the irradiation of B6.Ly5.2 mice at various doses to prepare an immunosuppressive partner. Irrespective of irradiation, lymphocytes and other hematopoietic cells in the bone marrow and lymphocytes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Local expansion is therefore unlikely to account for the majority of intrahepatic lymphocytes, unless turnover of cells and recirculation are ignored. Experiments in parabiotic mice suggested that CD3 intermediate NK1.1Cintrahepatic T cells do not recirculate, whereas 30-45% of conventional intrahepatic T cells and of cells from lymphoid organs were exchanged [20]. However, data from both animal and clinical liver transplantation have clearly shown that various subsets of donor-derived intrahepatic lymphocytes appear in the circulation and in other recipient tissues [21,22].…”
Section: Intrahepatic Lymphocytes Develop and Mature Locallymentioning
confidence: 97%
See 1 more Smart Citation
“…Local expansion is therefore unlikely to account for the majority of intrahepatic lymphocytes, unless turnover of cells and recirculation are ignored. Experiments in parabiotic mice suggested that CD3 intermediate NK1.1Cintrahepatic T cells do not recirculate, whereas 30-45% of conventional intrahepatic T cells and of cells from lymphoid organs were exchanged [20]. However, data from both animal and clinical liver transplantation have clearly shown that various subsets of donor-derived intrahepatic lymphocytes appear in the circulation and in other recipient tissues [21,22].…”
Section: Intrahepatic Lymphocytes Develop and Mature Locallymentioning
confidence: 97%
“…The best evidence for thymus-independent development in the liver comes from the unconventional intrahepatic lymphocytes, such as NK and NKT cells, which are found in higher frequencies here than in other organs [20]. However, NK and NKT cells can also be found within blood and other organs, such as the spleen, in significant numbers [6,26], and classical abTCR NKT cells as well as nonclassical gd TCR NKT cells can be recruited into the liver through an LFA-1-dependent mechanism involving binding to neighboring liver-resident NK cells [31,32].…”
Section: Intrahepatic Lymphocytes Develop and Mature Locallymentioning
confidence: 99%
“…Further investigation of this population revealed that development and differentiation of these cells take place in the liver [72,73]. It has been proposed that the resident liver lymphocytes play a crucial role in coping with the immunological challenges and mediating tolerance by regular exposition to dietary antigens, foreign organisms, toxins and pathogens [70,74].…”
Section: The Liver-lymphoid or Non-lymphoid Organ?mentioning
confidence: 98%
“…[9][10][11][12] Murine analog of iNKT cells expresses V␣14i canonical T-cell receptor (TCR)-␣ chain and has been demonstrated to be a distinct sublineage of T cells since its development depends on a number of genes, which are dispensable for conventional T cells. 1,[13][14][15] Although early reports suggested that extrathymic developmental pathway may exist for murine iNKT cells, [16][17][18][19][20] recent studies have excluded such a possibility. [21][22][23][24] Current models suggest that V␣14i cells appear as a result of spontaneous TCR-␣ rearrangement at the stage of CD4 CD8 double-positive (DP) thymocyte followed by CD1d-directed positive and negative selection and maturation of CD4 ϩ single-positive (SP) and CD4 CD8 double-negative (DN) V␣14i T cells.…”
Section: Introductionmentioning
confidence: 99%